2011
DOI: 10.1111/j.1570-7458.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of selected pathogens of cotton within the southern green stink bug

Abstract: Southern green stink bugs, Nezara viridula (L.) (Hemiptera: Pentatomidae), are pests of cotton recently shown to ingest, retain, and introduce some pathogens of cotton into bolls. The objective of this study was to determine where pathogen colonization occurs in N. viridula after ingestion. Laboratory‐reared adult N. viridula were fed sterile green beans soaked in water (control) or beans previously soaked in a suspension of one of three opportunistic bacterial pathogens [Pantoea agglomerans (Ewing & Fife), Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…However, detection of the marked bacteria and general bacteria in similar quantities in each of the stadia suggested that the marked bacteria were able to colonize the insect without compromising the general bacterial fauna. Esquivel and Medrano (2012) also observed similar densities of marked bacteria and innate bacteria in alimentary canal of adults. Therefore, a competitive exclusionary effect for colonizing the insect likely does not exist between the introduced marked bacteria and innate bacterial fauna.…”
Section: Discussionsupporting
confidence: 72%
“…However, detection of the marked bacteria and general bacteria in similar quantities in each of the stadia suggested that the marked bacteria were able to colonize the insect without compromising the general bacterial fauna. Esquivel and Medrano (2012) also observed similar densities of marked bacteria and innate bacteria in alimentary canal of adults. Therefore, a competitive exclusionary effect for colonizing the insect likely does not exist between the introduced marked bacteria and innate bacterial fauna.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, in the current study, P. agglomerans Sc1R (and innate microbiota) cells evidently were residing in the midgut of the various stadia. Although, previous work showed that, in adult N. viridula, P. agglomerans Sc1R can also colonize in the rostrum and the head [10].…”
Section: Plos Onementioning
confidence: 92%
“…The food items were replaced twice per week at 3-4 d intervals. Also, at each food replacement, available egg clutches were harvested and placed in modified plastic containers as previously described [10], Esquivel & Medrano (2012). Nymphs resulting from these egg clutches and colony insects were held in a walk-in environmental chamber at 26.7±1.0˚C and 14:10 [L:D] photoperiod.…”
Section: Insect Sourcementioning
confidence: 99%
“…Herbivorous sucking bugs often feed upon plant reproductive structures and can therefore directly impact plant fitness and crop yields. Many sucking bugs such as the plant bugs (Miridae) and stink bugs (Pentatomidae) can be major agricultural pests because of their impact on plants either directly through feeding damage or indirectly by vectoring plant pathogens (Greene et al ., ; Esquivel & Mowery, ; Esquivel et al ., ; Brewer et al ., ; Esquivel & Medrano, ). In cotton, the relatively recent rise of plant bugs and stink bugs as pests is attributed in part to decreased application of broad‐spectrum insecticides, because of the use of Bt plants targeting caterpillars (Zhao et al ., ) and successful pest mitigation strategies such as the boll weevil eradication program (Smith, ; Allen, ; Deguine et al ., ).…”
Section: Introductionmentioning
confidence: 99%